Circadian regulation and molecular role of the Bsx homeobox gene in the adult pineal gland. Issue 2 (30th December 2019) - Carstensen, Mikkel B.; Hertz, Henrik; Bering, Tenna; Møller, Morten; Rohde, Kristian; Klein, David C.; Coon, Steven L.; Rath, Martin F.
Abstract: The pineal gland is a neuroendocrine organ responsible for production of the nocturnal hormone melatonin. A specific set of homeobox gene‐encoded transcription factors govern pineal development, and some are expressed in adulthood. The brain‐specific homeobox gene ( Bsx ) falls into both categories. We here examined regulation and function of Bsx in the mature pineal gland of the rat. We report that Bsx is expressed from prenatal stages into adulthood, where Bsx transcripts are localized in the melatonin‐synthesizing pinealocytes, as revealed by RNAscope in situ hybridization. Bsx transcripts were also detected in the adult human pineal gland. In the rat pineal gland, Bsx was found to exhibit a 10‐fold circadian rhythm with a peak at night. By combining in vivo adrenergic stimulation and surgical denervation of the gland in the rat with in vitro stimulation and transcriptional inhibition in cultured pinealocytes, we show that rhythmic expression of Bsx is controlled at the transcriptional level by the sympathetic neural input to the gland acting via adrenergic stimulation with cyclic AMP as a second messenger. siRNA‐mediated knockdown (>80% reduction) in pinealocyte cultures revealed Bsx to be a negative regulator of other pineal homeobox genes, including paired box 4 ( Pax4 ), but no effect on genes encoding melatonin‐synthesizing enzymes was detected. RNA sequencing analysis performed on siRNA‐treated pinealocytes further revealed that downstream target genes of Bsx are mainly involved in developmental processes. Thus, rhythmic Bsx expression seems to govern other developmental regulators in the mature pineal gland.